LEXICAL-SEMANTIC PROBLEMS IN ENGLISH-UZBEK TRANSLATION AND THEIR ELIMINATION - Kamoliddinova Munisa Bohodir qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article discusses the problems of translation of lexical and lexical-semantic units from English to Uzbek and ways to solve them.